Surface shape measurements with high-level point density and numerical modeling of untechnical objects - Garibal’di, A. V.; Kulesh, V. P. (Automation and remote control, 2011)
The structure and operation of videogrammetric system with cutting light plane (3D scanner) is briefly described; this system allows to measure surface shape of the object with high-level point density. The procedure and results of measuring system calibration are discussed. Measurement error estimates are provided. The processing algorithm for the measurement results, as well as numerical modeling algorithm for the studied object based on the results are presented. Brief description of using the stated approach to create the bank of numerical models of archeological objects is given. Finally, we consider the results of applying the approach to reconstruct the shape of ancient bath dated IV–V century BC.